Efektivitas Pendidikan Kesehatan Melalui Media Kartu Cinta Anak Tentang 1000 Hari Pertama Kehidupan dalam Meningkatkan Pengetahuan Pasangan Calon Pengantin di KUA Kecamatan Jatinangor - Dian Nurlaela; Puspa Sari; Neneng Martini; Merry Wijaya; R. Tina Dewi Judistiani (Sekolah Vokasi Universitas Gadjah Mada, 2018)
Background: The First Thousand Days of Life (Golden Period) is a very critical period from the moment of conception to infant aged 2-year-olds which, if not properly utilized, will have permanent damage such as impaired physical growth, intelligence, and non-communicable diseases. The soon-to-be married couple is one of the target groups to improve health quality in the First 1000 Days of Life (1000 FDL). Improvement of the quality of health can be achieved by providing health education using Kartu Cinta Anak (KCA). Objective: The purpose of this study is to determine the effectiveness of health education using KCA about 1000 FDL in improving the knowledge of soon-to-be married couple in KUA Jatinangor Sub District.Methods: This research used a quantitative method with pre-experimental design in the form of pretest-posttest, conducted in July 2017. The sample of the research are soon-to-be married couples registered in KUA Jatinangor sub district who have never been married and have not had children. The total number of samples are 34 pairs of respondents. Data analysis using Paired Sample t-test.Results: The results showed that the use of KCA was effective in improving soon to be married couple’s knowledge about 1000 FDL, with Paired Sample t-test value of <0,05 (P = 0,000), suggesting that there was significant difference in soon-to-be married couple’s knowledge before and after health education.Conslusion: The conclusion of this research is the use of KCA is effective in improving the knowledge of soon-to-be married couple about the First 1000 Days of Life.